2018
DOI: 10.1111/cns.12838
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal resting‐state functional connectivity in posterior cingulate cortex of Parkinson's disease with mild cognitive impairment and dementia

Abstract: When patients transition from PD-NCI to PD-MCI, there appears to be an increase in functional connectivity in the PCC, suggesting an expansion of the cortical network. Another new network (a compensatory prefrontal cortical-cerebellar loop) later develops during the transition from PD-MCI to PDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 33 publications
(67 reference statements)
8
53
0
Order By: Relevance
“…Interestingly, functional connectivity deterioration in posterior cortical regions has been associated with progression of cognitive impairment over 3 years in a longitudinal fMRI study [98]. Moreover, alterations within the DMN have been shown to be more relevant in PD patients with MCI [99][100][101] and with dementia [97,[101][102][103], further supporting the potential role of RS-fMRI to depict a sensitive and specific biomarker of dementia in PD for prognostic and disease-monitoring purposes.…”
Section: Premotor Phase and Non-motor Symptoms Correlatesmentioning
confidence: 89%
“…Interestingly, functional connectivity deterioration in posterior cortical regions has been associated with progression of cognitive impairment over 3 years in a longitudinal fMRI study [98]. Moreover, alterations within the DMN have been shown to be more relevant in PD patients with MCI [99][100][101] and with dementia [97,[101][102][103], further supporting the potential role of RS-fMRI to depict a sensitive and specific biomarker of dementia in PD for prognostic and disease-monitoring purposes.…”
Section: Premotor Phase and Non-motor Symptoms Correlatesmentioning
confidence: 89%
“…In addition, studies have found that Parkinson's disease (PD), Huntington's disease, schizophrenia, major depressive disorder, type 2 diabetes mellitus (T2DM), chronic obstructive pulmonary disease (COPD), lung cancer following chemotherapy, hepatic encephalopathy, kidney deficiency syndrome, and other diseases can also cause CI (70)(71)(72)(73)(74)(75)(76)(77)(78)(79), but the relationships between these diseases and cognitive function and the pathogenesis of CI are still unknown, necessitating further in-depth studies. rs-fMRI will play an important role in the exploration of these unknown areas.…”
Section: Application Of Rs-fmri In Mild Traumatic Brain Injury (Mtbi)mentioning
confidence: 99%
“…FMRI studies showed that all the resting‐state functional networks underlying the main cognitive functions, such as the default mode, dorsal‐attention, frontoparietal, salience, and associative visual networks, are altered in patients with PD . Also, functional connectivity disruption of specific brain areas such as the temporal, parietal, and occipital regions has been found in PD patients with memory and visuospatial deficits …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in early PD patients, the disrupted functional connectivity of the default mode network has been found to be predictive of cognitive decline with disease progression . Default mode network alterations worsen in PD patients with mild cognitive impairment (MCI) and dementia, and this process is associated with a progressive cognitive decline over a three‐year follow‐up in PD dementia patients . Interestingly, one study suggested that cognitively unimpaired PD patients showed a hyperconnectivity of cortical, limbic, and basal ganglia‐thalamic areas, which has been suggested as a compensatory mechanism preceding cognitive decline …”
Section: Introductionmentioning
confidence: 99%